Moral constraints, social norm enforcement and strategic default in weak and strong economic conditions - Martin Brown; Jan Schmitz; Christian Zehnder (Swiss National Bank, Study Center Gerzensee, 2023)
We report data from a laboratory experiment studying the behavioral mechanisms which contribute to the increase in strategic defaults during an economic crisis. In our experiment, subjects can default on an outstanding loan, but moral constraints and social norm enforcement may provide incentives to repay. We exogenously vary the state of the economy: In the weak economy more borrowers are forced to default than in the strong. Our data reveal two main effects of an economic contraction: First, weak economic conditions seem to soften moral constraints as solvent debtors strategically default more often. Second, weak economic conditions undermine social norm enforcement. The decrease in norm enforcement, however, is not caused by a break-down of the repayment norm itself, but rather is a consequence of the additional informational uncertainty in weak economic conditions. In a weak economy peers are reluctant to sanction, because the risk of harming innocent debtors is higher.
Keywords: G01; C91; D91; G41; 330; Strategic Default; Moral Constraints; Social Norms